2009
DOI: 10.1111/j.1479-828x.2009.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sleep deprivation is a risk factor for small for gestational age: A cohort study

Abstract: Risk factors for SGA less than 5th centile were sleep deprivation and shift work and exposure to physical and chemical hazards during 2nd and 3rd trimesters, less walking hours and alcohol consumption during 3rd trimester. Poor weekly gestational weight gain may be considered as a predictor of delivering an SGA infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 36 publications
4
89
1
Order By: Relevance
“…Although the role played by oscillatory gene expression and circadian clocks during pregnancy remains unclear, gestational chronodisruption may be regarded as an adverse prenatal condition given that increased risk of miscarriage, preterm delivery, and low birth weight have been consistently reported in shift worker women (1,8,9,21,53). In fact, despite the fetal suprachiasmatic nucleus not yet being the master circadian clock (at least in the conventional way it works during adulthood), several fetal organs seem to operate as peripheral oscillators in the rat (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role played by oscillatory gene expression and circadian clocks during pregnancy remains unclear, gestational chronodisruption may be regarded as an adverse prenatal condition given that increased risk of miscarriage, preterm delivery, and low birth weight have been consistently reported in shift worker women (1,8,9,21,53). In fact, despite the fetal suprachiasmatic nucleus not yet being the master circadian clock (at least in the conventional way it works during adulthood), several fetal organs seem to operate as peripheral oscillators in the rat (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…[2] In contrast, rotating shift work exposure can compromise the health of early middle-aged female workers, [3][4][5] an important population giving birth in industrialized countries. Although studies in some workplace settings have found adverse effects of shift work exposure on reproductive disorders of female employees [6,7] and on birth weight of fetuses, [8,9] few studies have investigated these effects in semiconductor manufacturing factories.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, chronodisruption (i.e., a significant disturbance of the temporal organization of endocrinology, physiology, metabolism and behavior) along pregnancy has been associated with an increased risk not only of miscarriage, but also preterm delivery and low birth weight [2][5]; both strong predictors of chronic disease later in life [6][7]. Conceivable, both the maternal and fetal circadian system are the targets of developmental chronodisruption.…”
Section: Introductionmentioning
confidence: 99%